IMPACT OF BLOCKCHAIN TECHNOLOGY FOR MODIFICATION OF THE SUPPLY CHAIN MANAGEMENT IN ENERGY MARKETS - Afanasyev, Valentin Ya.; Lyubimova, Natalia G.; Ukolov, Vladimir F.; Shayakhmetov, Salavat R. (International Journal of Supply Chain Management, 2020)
Abstract? Supply chain management played a critical role in the electric power industrial chain optimization. The paper notes that in order to increase transparency and efficiency of settlements for electric energy, the introduction of intelligent metering systems is necessary. In order to achieve efficiency, transparency, data security and reduce transaction costs abroad, blockchain technologies that have both positive and negative characteristics have begun to be actively introduced. Similar aspirations are realized in Russia, where smart metering devices are also installed everywhere for consumers of electric energy. At the same time, studies show that it is advisable to implement the implementation of blockchain technology only in conditions of decentralized electricity supply, since the principles of this technology are not compatible with management from a single center. In Russia, given the significant role of centralization in electricity supply chain and non-payment for energy, the presence of ?non-disconnected? consumers and a very modest share of renewable energy, the possibilities for using blockchain technology are very limited. This necessitates the search for effective ways to use blockchain technology, taking into account the current circumstances.